CDf International Congress : proceedings : actes, actas : actes, Barcelona Jun. 2013 - Mireia Freixa (Col·lecció Singularitats, 2015)
[eng] In 2013 the magazine coupDefouet reached its first decade of existence. As a way of celebrating this, the Art Nouveau European Route - the association of cities and other local institutions for the promotion and diffusion of Art Nouveau heritage that created the magazine - organised a magnificent international congress as a framework for scientific exchange and raising public awareness. The first coupDefouet International Congress on Art Nouveau was held in Barcelona, the city from which coupDefouet is published and one of the undisputable world capitals of Art Nouveau. This volume of the Singularitats series comprises the proceedings of that event. [cat] L'any 2013 va fer deu anys de l'aparició de coupDefouet, la revista de la Ruta Europea del Modernisme, una associació de municipis i altres entitats locals per a la promoció i la difusió del patrimoni modernista o Art Nouveau. Per commemorar-ho, s'organitzà un congrés internacional amb l'objectiu de contribuir al coneixement científic i la difusió d'aquest moviment artístic. El primer Congrés Internacional coupDefouet se celebrà a Barcelona, la ciutat en què s'edita coupDefouet i una de les capitals indiscutibles de l'Art Nouveau. En aquest volum de Singularitats s'apleguen les actes d'aquell esdeveniment.